Philip K. Dick’s Decohering and Recohering Worlds: The Cases of Ubik and The Man in the High Castle - Jakovljević, Mladen; Ćirković, Milan (Atlantis. Journal of the Spanish Association for Anglo-American Studies, 2023)
Philip K. Dick’s novels Ubik and The Man in the High Castle explore the idea of the multiplicity of realities, which can be understood better if interpreted from a cosmological point of view. The scientific principles of decoherence, as formulated by H. Dieter Zeh and Hugh Everett III, shed light on the nature of these fictional worlds, their creation and dissolution and their perception by both the protagonists and the reader. Ontological puzzles of the quantum world, based on the rejection of the special status of an observer in physical reality and fractal branching of the universe, offer insights into the mechanisms at work in these two novels. Decoherence may be the key to understanding the disintegrating borders between realities in both novels, which are manifested as worlds in superposition. However, the rules of this scientific principle are radically challenged by the emergence of what could be termed the agents of re-coherence. These agents reveal the existence of alternate realities in the novels, as well as the process of the violation of the decoherence principle. Not only are these occurrences interesting from both a scientific and artistic point of view, they also reveal the realities in the novels as being far more coherent than they seem on the surface and interpretable as literary parallels to thought experiments conceived as possible explanations of the quantum world theory.